Implementasi Program Remunerasi Dalam Rangka Reformasi Birokrasi Dan Peningkatan Kinerja Aparatur Di Lingkungan Sekretariat Daerah Provinsi Maluku Utara - Sangadji, Nini; Pribadi, Ulung (Universitas Muhammadiyah Yogyakarta, 2015)
Results of this study concluded that the performance-and activity-based remuneration program have not been able toachieve the goal of improving the poor performance of civil servants in Unit Sekertariat Daerah Provinsi Maluku Utarabecause it cannot still be implemented well. The constraint found in the implementation was inconsistency between therealization of program and the guidelines of program. It is impressed that the implementation of program was only toperforming the formal obligations and not oriented to the goals of program for improving the performance of civilservants in Unit Sekertariat Daerah Provinsi Maluku Utara. The factors influencing the implementation of the programwere the low commitment of implementing staff in achieving the goals of the program, the weak supervision of theprogram, and the poor design of program with many weaknesses.